Pengembangan Bahan Ajar Laju Reaksi Berbasis STEM-PBL pada Mata Kuliah Dasar Ilmu Kimia - Mutiara Agustina Nst.; Dwy Puspita Sari; Ani Sutiani; Mutia Ardila (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to develop teaching materials on reaction rates based on the STEM-Problem Based Learning (STEM-PBL) approach and to assess their validity and practicality, ensuring they are suitable for use in a basic chemistry course. The study employed the Research and Development (R&D) method using the Plomp model, which encompasses the stages of preliminary investigation, design, product development, evaluation, and revision. The research involved three expert validators and 30 students from the Chemistry Education Study Program. Data collection instruments included validation sheets and practicality questionnaires. Validation results indicated that the teaching materials fell into the "highly valid" category, with average scores of 90 for content, 90.8 for language, and 88.3 for graphics. Practicality test results showed that the developed materials were "highly practical," achieving scores of 87 for ease of use, 88.5 for presentation appeal, and 90.5 for usefulness. The findings demonstrate that the STEM-PBL-based reaction rate teaching materials meet the criteria for high validity and practicality, making them suitable as learning resources for basic chemistry courses. This study was limited to assessing the product's validity and practicality.